PeerLoom: peer-to-peer skill exchange platform for university students / Farrah Othman … [et al.] - Othman, Farrah; Kasim, Syazliana; Mohd Sharip, Sharfizie; Md Kamdari, Nor’Azurah; Ab Wahab, Shahrul Amri (Faculty of Computer and Mathematical Sciences, 2023)
In the dynamically evolving educational landscape, the proposed PeerLoom (Peer-to-Peer Skill Exchange Platform) for university students emerges as an innovative and empowering project. This platform aims to harness the diverse and unique skills and knowledge present within the student community, creating an accessible space for the exchange of expertise and learning. At its core, the platform operates as a digital marketplace where students can offer their skills and knowledge in various disciplines, and in return, learn from their peers in areas they seek to improve or explore. From academic subjects like mathematics and science to non-academic skills like photography, personal grooming, makeup skills, coding, or language learning, the platform embraces a wide spectrum of knowledge areas. This inclusive approach ensures that all students, regardless of their field of study, can share and gain skills. Functionality is enhanced with a user-friendly interface, advanced search features, and a robust rating and review system. These features allow students to navigate and find the right skill exchange opportunities easily. The platform also supports different formats of learning, including one-on-one sessions, group learning, and online tutorials, offering flexibility and convenience to its users. Beyond mere skill exchange, this platform fosters a collaborative learning environment, promoting interaction, networking, and community building among students. It enhances the students' skillsets and cultivates a culture of collective growth and mutual support, essential attributes for their future careers and personal development. In addressing the multifaceted needs of the student community, the PeerLoom stands out as a pioneering project, poised to revolutionize learning and skill development in universities worldwide.